Screening for fifteen vegetable soybean [Glycine max (L.) Merrill] accessions for morpho-agronomy and CAT and SOD expression under mineral topsoil and amended-bris soil of Malaysia - Siti Nurul Farhana binti Abu Bakar (Kulliyyah of Science, International Islamic University Malaysia, 2017)
Consumption of highly nutritious vegetable soybean (Glycine max (L.) Merrill) as a fresh vegetable and snack in Malaysia is not as popular as in other Asian countries due to its lack of availability in Malaysian market. Thus, this study was carried out to evaluate the morpho-agronomic characteristics of fifteen accessions of vegetable soybean introduced from the Asian Vegetable Research and Development Center (AVRDC), Taiwan. The ultimate objective of the study is to identify potential accessions for planting under Malaysian environments. The accessions were planted in poly bags containing mineral topsoil and amended-bris soil at International Islamic University Malaysia (IIUM) Kuantan, Pahang. Among eight agronomic traits studied, seed and pod numbers per plant were taken as the yield determinant in selecting the potential accessions. From the results, AVRDC's vegetable soybean lines AGS190 and AGS346 were found to be the most adapted accessions under both mineral topsoil and amended-bris soil conditions. In addition, gene expression study of antioxidative enzymes (catalase, CAT and superoxide dismutase, SOD) was also conducted on the fifteen accessions. These genes are involved in plant defence mechanisms towards biotic and abiotic stresses. The expression of antioxidative genes depends on several factors such as plant species and genotype, plant development and metabolisms and stress sensitivity and duration. Using a real-time polymerase chain reaction (qPCR), the expression of CAT and SOD of fifteen accessions of vegetable soybean under both types of soil were quantified and compared. Lines AGS292 and AGS430 showed the highest CAT and SOD expressions, respectively under mineral topsoil. Under amended-bris soil, line AGS429 showed the highest CAT expression while line AGS472 showed the highest SOD expression. The results indicated a unique pattern of CAT and SOD expressions in fifteen accessions under different soil types. Findings from this study will contribute to future cultivation of vegetable soybean as well as for its future development and improvement programs in Malaysia.